Investigating wastewater flow from a gated community to disaggregate indoor and outdoor water use - Du Plessis, J. L.; Faasen, B.; Jacobs, H. E.; Knox, A. J.; Loubser, C. (Journal of water, sanitation, and hygiene for development, 2018)
Disaggregating residential water use into components for indoor and outdoor use is useful in view of water services planning and demand management campaigns, where outdoor use is often the target of water restrictions. Previous research has shown that individual end-use events can be identified based on analysis of the flow pattern at the water meter, but such studies are relatively complex and expensive. A basic method to disaggregate the indoor–outdoor water use would be useful. In addressing this problem, a technique was employed in this study to disaggregate indoor–outdoor water use based on knowledge of the wastewater flow, with assumptions that link indoor use to wastewater flow. A controlled study site in a gated community, with small bore sewers, was selected to allow certain assumptions to be validated. The results provide insight into the monthly indoor and outdoor water use of homes in the study area, and show how wastewater flow could be used to assess outdoor use. Outdoor use was found to represent up to 66% of the total household water use in January, accounting for ∼58% of the total annual water use in the study area 2016.